Long-term tests duration reduction for PEMFC μ-CHP application - Pahon, E.; Morando, S.; Petrone, R.; Péra, M.-C.; Hissel, D.; Yousfi-Steiner, N.; Jemei, S.; Gouriveau, R.; Chamagne, D.; Moçotéguy, P.; Zerhouni, N. (International journal of hydrogen energy, 2017)
Proton exchange membrane fuel cells (PEMFC) are extremely promising devices. Nevertheless some technological constraints concerning system durability and reliability costs, still limit their large-scale production. In this framework, lifetime prediction and durability enhancement studies are mainly concerned. To solve this issue, methods based on Prognostic and Health Management (PHM) are developed. It is worth noting that these methods usually require to establish a consistent database concerning the system ageing referring to specific mission profiles. To this purpose, long-term tests are commonly performed. Among different applications, this paper will focus on two micro-cogeneration (μ-CHP) durability tests, based on the same load demand. The first test is realized in 1000 h while the second one is reduced to 500 h resulting in a compressed profile. We observed that the respective global voltage degradation rates are similar. Consequently a reflection is proposed to support accelerated tests protocol development. •The ageing effects induced by a real load profile are taking into account by making experimental tests.•The influence of the steady state conditions durations, OCV and sudden load variations are analyzed.•The effects of the long-term test duration reduction on voltage decay are analyzed too.•New methods can be proposed to reduce long duration tests by increasing the real load cycle frequency.•Results with experimental data verify the effectiveness of the method.